Design and Synthesis of 3‐Trifluoromethyl‐3H‐pyrazoles and Further Investigations of Their Transformation to 1H‐Pyrazoles. Issue 34 (27th October 2014) - Sha, Qiang; Liu, Haixuan; Wei, Yunyang
Abstract: An efficient intramolecular cycloaddition strategy for the synthesis of trifluoromethyl‐substituted 3 H ‐pyrazoles was developed. Subsequently, their wide applications were demonstrated: they (1) react with dioxane by a radical process and (2) undergo [1, 5] sigmatropic rearrangements. These applications are useful as the products were obtained in high yields and with excellent regioselectivity. Abstract : The synthesis of trifluoromethyl‐substituted 3 H ‐pyrazoles by an intramolecular cycloaddition strategy is developed. Subsequently, their wide applications are demonstrated: they (1) react with dioxane by a radical process and (2) undergo [1, 5] sigmatropic rearrangements. The products are obtained in high yields and with excellent regioselectivity.